Transformation of HIV/AIDS education through technology: assessing the success of GEBRAK SETIA among teenagers in Surakarta City - Oktavia, Nindi; Pramesti, Ardhia Putri; Fitriani, Neng Resi; Setyani, Rizka Ayu (Journal of Community Empowerment for Health, 2026)
Introduction: The increasing prevalence of HIV/AIDS among Indonesian adolescents highlights the urgency of implementing innovative approaches in health education. This study explores the introduction of the digital-based GEBRAK SETIA (Gerakan Bersama Kader Satgas Remaja Tanggap HIV/AIDS) program through the EKSTRIM website platform as a youth-centered educational solution in Surakarta City. The program focuses on improving adolescent literacy about HIV/AIDS, reducing social stigma, and encouraging proactive prevention behavior through the involvement of peer educators using digital media.Methods: This study employed a qualitative descriptive design. Data were collected through testimonial video interviews, participatory observation, and documentation of role play and group discussions. A total of 40 adolescents aged 10-17 years, selected using purposive sampling from the Satgas Remaja in Semanggi, Surakarta, participated in a single-session activity held on November 5, 2023. The session, lasting 90-120 minutes, included peer-led education, website navigation, Q&A, and interactive role play. Content analysis was conducted to identify recurring themes, ensuring credibility through data triangulation and peer debriefing.Result: The EKSTRIM platform’s anonymous self-screening tool enabled participants to confidentially and independently evaluate their HIV risk. Screening outcomes indicated that 12 of 40 adolescents (30%) were classified as high risk, while 28 (70%) were in the low or no risk category. Educational sessions, delivered by peer educators in collaboration with the AIDS Prevention Commission (KPA) Surakarta, were associated with improved understanding of the distinction between HIV and AIDS, transmission routes, prevention strategies, and access to digital consultation services. Participation in QnA activities and role-play exercises was linked to increased confidence in conveying prevention messages and a clearer grasp of relevant strategies. Interview data further suggested a reduction in stigmatizing attitudes toward people living with HIV/AIDS (ODHA) and a stronger inclination to undergo or recommend HIV testing, reflecting greater motivation for early detection. Minor scheduling constraints were effectively addressed through coordinated planning, ensuring smooth program delivery.Conclusions: The GEBRAK SETIA program proved effective in educating adolescents, promoting behavioral change, and reducing HIV/AIDS related stigma. It is recommended that this program be expanded to other high-prevalence areas, supported by the development of more interactive digital features and integration of HIV/AIDS education into school curricula to ensure a broader and more sustainable impact